The World Bank Group in Bangladesh, Fiscal Years 2011–20 : Country Program Evaluation - Independent Evaluation Group (Washington, DC : World Bank, 2022)
This Country Program Evaluation (CPE) assesses the development effectiveness of the World Bank Group’s engagement with Bangladesh during the past decade (fiscal year [FY]11–20) and provides lessons to inform the next Bank Group supported strategy with Bangladesh and to countries facing similar challenges. The Bank Group made important contributions over the past decade to help Bangladesh address several of its development challenges. Most notable include increasing power generation capacity, improving access to clean energy, all season roads, primary and secondary education, reducing child and maternal mortality and improving financial inclusion. However, achievements fell short in several areas, including insufficient investment in data and measurement particularly on learning outcomes and limited progress on regional connectivity. In other areas, domestic vested interests prevailed resulting in little progress in improving the business environment, natural resource management, banking reform and tariff reform. Bank Group support adapted in response to changing circumstances following the Padma Bridge cancellation by reallocating resources to sectors in which the Bank Group had more traction and a long-standing history of effective engagement. However, rising fiscal vulnerabilities received insufficient attention. Despite a deteriorating trend in institutional quality and economic management and declining core IDA allocation, the Bank Group significantly increased financing to Bangladesh, including through IDA’s Scale Up Facility. Key lessons include: (i) Rebalancing the portfolio in the face of a difficult political economy helped the Bank Group remain relevant in Bangladesh; (ii) Where reform is deemed critical to sustain development progress but government commitment is weak or absent, continued targeted analysis of key development constraints can help prepare the ground for future action when a window of opportunity presents itself; (iii) Measuring improvements in the quality of education requires deliberate and ongoing investment in data collection; (iv) Increasing overall IDA financing in the context of deteriorating CPIA rating raises a question about the significance that IDA assigns to measures of institutional quality and governance; (v) Given underlying concerns with data quality and coverage, the World Bank might have been more qualified in its public statements about the quality of the macroeconomic framework; and (vi) Financial Sector Assessment Program (FSAP) arrangements between the World Bank and the IMF constrain the ability of the World Bank to provide comprehensive and timely assessments of financial sector vulnerabilities in nonsystematically important economies.